Nice Cake Sdn. Bhd. / Mohd Erdi Abdul Rahman, Syaiful Bakhtiar and Noor Azrul Mat Saad. - Abdul Rahman, Mohd Erdi; Jamn, Syaiful Bakhtiar; Mat Saad, Noor Azrul (2002)
ICE Cake Sdn Bhd is a new company which basically operating the installation of all cakes and cookies that relates to it. The operation of the company will start within 1 of December 2002. the location of the business is at Kangar. We have chose Sdn. Bhd. because of the characteristic itself. It limits the number of its member to only 50 persons. This means it easier to be control. It also prohibits any invitation to the public to subscribe for any share in the company. The company entity was separated from its shareholders. In this way, it will not give extra burden to the shareholders. Because of cakes and confectionary is the latest food and also a famous food, the business will face a hard way in giving a good service. The competitors are still few, therefore the company will expand in a short time. In addition, the advantages that cakes and confectionary offers will make people easy and no need to cook at their house especially for launch hour and becoming festival.